Vliv diferenčního skupinového zpoždění na chybovost optického kanálu - Kyselák, Martin; Dorociak, Petr (International Society for Science and Engineering, o.s., 2008)
This article describes the impact of polarization mode dispersion on optical fibre link. There is analysed PMD effect of bit error rate on optical channel, on modulating signal and on close of eye diagram. All article calculates only with losses that are caused of polarization mode dispersion. It is not calculated with losses that are caused of chromatic dispersion and attenuation.

Článek popisuje vlivy diferenčního skupinového zpoždění na optický komunikační systém. Dále vysvětluje jeho vliv na modulační signál, chybovost optického kanálu, a pokles diagramu oka. V celém článku se počítá pouze se ztrátami, které způsobuje polarizační vidová disperze. Ztráty způsobené útlumem a chromatickou disperzí jsou zanedbávány.
The Differential Group Delay Impact on Optical Channel Bit Error Rate
Keywords: diferenční skupinové zpoždění; vlákno; disperzní vlivy; chybovost; diagram oka; Differential Group Delay; optical fibre; dispersion; BER; Eye Diagram